Hubungan Rasio Neutrofil Limfosit terhadap Mortalitas dan Lama Rawat Inap pada Pasien Sepsis di Ruang Intensif RSD dr. Soebandi Jember - Arya Adib Toni (Fakultas Keperawatan, 2025)
Sepsis remains a critical global health burden, with disproportionately high Intensive Care Units (ICU) mortality rates. This condition is driven by dysregulated neutrophil and lymphocyte responses, which cause organ failure and prolonged hospitalization. Despite the neutrophil lymphocyte ratio's (RNL) potential as an accessible prognostic tool, its associations with mortality and length of stay (LOS) show inconsistent evidence across existing literature. The purpose of this study was to determine the correlation between RNL and both mortality and length of stay (LOS) in patients with sepsis in the Intensive Care at RSD dr. Soebandi Jember. Methods: A retrospective cross-sectional study was conducted using total sampling (N = 102 from 134 medical records of sepsis patients in the intensive care unit who met the inclusion and exclusion criteria during January 2020–August 2024). Data analysis employed descriptive statistics, binary logistic regression, and Spearman rank tests. Results: Participants had a median age of 55.5 years, with male predominance (53.9%) and pneumonia as the main comorbidity (26.47%), mortality of 74 cases (72.5%), and a median hospital stay of 4 days. Bivariate analysis employed logistic regression binary for the relationship between RNL and mortality showed a p-value of 0.042 and an odds ratio (OR) of 1.074. The OR value of 1.074 indicates that a 1-unit increase in RNL is associated with a 7.4% increase in mortality risk. The Spearman rank test for the relationship between RNL and Intensive Care LOS showed a p-value of 0.005 and a correlation coefficient (r) of 0.255, though the correlation was considered weak. Conclusion: RNL has been demonstrated to be significantly associated with increased mortality and prolonged Intensive Care stays in sepsis patients, although its correlation with LOS is weak.
Entry oleh Arif 2026 April 01
Keywords: Length of Stay; Mortality; Neutrophil Lymphocyte Ratio; Sepsis